DETERMINATION OF SOME PHYSICAL PROPERTIES OF THREE GROUNDNUT VARIETIES (Nigerian Journal of Technology, 2005)
The determination of physical properties of some groundnut varieties is of paramount importance in the design and development of systems and machines for the shelling of groundnuts. Three varieties of groundnuts namely ICGV-SM-93523, RMP-9 and RMP- 12 were collected and some of the physical properties, such as weight, angle of repose, coefficient of friction, bulk density, size, shape and moisture content were determined. The angle of repose for the three varieties was found to range from 27.5 - 29.50 f or tire pods, 20.3 - 20.80 for the seeds and 33.7 - 36.00 for the shells. Coefficient of friction averaged 0.56 on wood and 0.41 on galvanized steel for the three varieties of groundnut pods. The moisture contents of the pods, seeds and shells were found to be 7.4%, 6.4% and 11.3% (wet basis) on the average respectively. The results also showed that groundnut pods and seeds were neither round nor spherical, but may be oblong in shape. Statistical single-factor analysis of variance (ANOVA) carried out to compare the mean values of the physical properties of the three varieties of groundnuts showed that there were no significant varietal differences at p£ 0.5 probability level. Tire implication of no significant varietal difference at p£ 0.5 is that one machine can conveniently handle the shelling operation for the three varieties of groundnuts.